2012
DOI: 10.1152/japplphysiol.00481.2012
|View full text |Cite
|
Sign up to set email alerts
|

Heliox increases quadriceps muscle oxygen delivery during exercise in COPD patients with and without dynamic hyperinflation

Abstract: Some reports suggest that heliox breathing during exercise may improve peripheral muscle oxygen availability in patients with chronic obstructive pulmonary disease (COPD). Besides COPD patients who dynamically hyperinflate during exercise (hyperinflators), there are patients who do not hyperinflate (non-hyperinflators). As heliox breathing may differently affect cardiac output in hyperinflators (by increasing preload and decreasing afterload of both ventricles) and non-hyperinflators (by increasing venous retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 57 publications
1
46
1
Order By: Relevance
“…Although in normal subjects, this phenomenon may not happen during submaximal exercise (Wetter et al 1999), it could occur in obese patient population characterized by a substantially higher work of breathing and increased metabolic demands. Some previous studies in COPD patients (Louvaris et al 2012;Vogiatzis et al 2011) also demonstrated a reduced expiratory muscle activity during He-O 2 breathing, with consequent improvements in cardiac output and "central" hemodynamics and further increases in peripheral muscle O 2 delivery.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although in normal subjects, this phenomenon may not happen during submaximal exercise (Wetter et al 1999), it could occur in obese patient population characterized by a substantially higher work of breathing and increased metabolic demands. Some previous studies in COPD patients (Louvaris et al 2012;Vogiatzis et al 2011) also demonstrated a reduced expiratory muscle activity during He-O 2 breathing, with consequent improvements in cardiac output and "central" hemodynamics and further increases in peripheral muscle O 2 delivery.…”
Section: Discussionmentioning
confidence: 82%
“…Also the calibration of the pneumotachograph was carried out by utilizing the experimental gas mixture (AIR or He-O 2 ). The possibility of this technical limitation was not mentioned in the studies by Brice and Welch (1983), Chiappa et al (2009), Esposito and Ferretti (1997), Louvaris et al (2012), Murphy et al (1969), Powers et al (1986).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, NIRS has been used in combination with the light-absorbing tracer indocyanine green dye to quantify regional blood flow in muscle and connective tissue during dynamic exercise in patients with COPD (352). Subsequent studies showed that respiratory muscle unloading improves locomotor muscle blood flow and oxygen delivery during exercise in patients with different patterns and degrees of dynamic hyperinflation (429,494). 31 P-NMR spectroscopy is a noninvasive method to evaluate high-energy compounds ATP, PCr, inorganic phosphate (Pi), and intracellular pH of single muscle groups during exercise and recovery (495).…”
Section: Assessment Of Muscle Oxygenation Using Near-infrared and Magmentioning
confidence: 99%
“…The authors selected in their recent study the lower resistance model, with a dead space above the mean reported in their previous study. 7 The potential clinical implications of this were not discussed in the paper. 2 Currently there are no studies that have evaluated the effect of a variable dead space and internal resistance of HMEs on patients during NIV.…”
Section: Hme Internal Dead Spacementioning
confidence: 99%
“…In order to make this classification, they adopted the criterion of an inspiratory capacity decrease of greater than 4.5% of the baseline value, or greater than 150 mL. 7 Cordonie et al considered DH to constitute any drop in inspiratory capacity, compared with the baseline value. This discrepancy in definition undermines the comparability of the findings as well as the ability of this classification to identify patients who will benefit from DH treatments.…”
Section: The Authors Respondmentioning
confidence: 99%